PELATIHAN “HOW TO WRITE A WINNING SCHOLARSHIP ESSAY” DI SMAK TUNAS BANGSA LIPPO CIKARANG - Rosari, Maria Dewi (DEVOSI, 2024)
The ability to write essays and speak English is the main qualification in the competition for scholarships and further study opportunities in the era of globalization. SMAK Tunas Bangsa Lippo Cikarang realizes the importance of this, especially for class XII students. In Indonesia, the increasing number of scholarship offers from the government and non-government organizations adds to the complexity of competition. However, not all applicants are successful due to inadequate essay writing and English skills. The "How to Write a Winning Scholarship Essay" course was designed as a response to this challenge. This training aims to provide effective essay writing skills and a wider English vocabulary. With a focus on writing structure and a persuasive point of view, this training prepares students to face academic challenges and competitive scholarships. The positive response from students and teachers shows the relevance of this training to the curriculum and the needs of students who will continue higher education and seek scholarships. Thus, investing in developing essay writing skills is a strategic step for SMAK Tunas Bangsa Lippo Cikarang students towards a successful and influential future.